Practical and theoretical implications of successfully doing difference in organizations - Pompper, Donnalyn, 1960- (International perspectives on equality, diversity and inclusion,, 2014)
Practical and theoretical implications of successfully doing difference in organizations is a book for managers and researchers passionate about follow-through on promises of workplace diversity across social identity dimensions, including age, class, culture, ethnicity, faith, gender, physical/psychological ability, sexual orientation, and more.